Electron tomography of muscle cross- bridge by regulatory light chain labelling with APEX2 - Mufeeda, Changaramvally Madathummal (2019)
Muscle contraction results from the cyclic interaction of myosin and actin by coupling energy of adenosine triphosphate (ATP) hydrolysis. During muscle contraction myosin and actin interact with each other through a structure called “cross-bridge”. Despite intense structural studies, the organisation of myosin cross-bridges on myosin filaments is not well understood. Myosin regulatory light chain (RLC) is one of the prominent proteins present at the lever arm domain of cross-bridges. Phosphorylation of RLC modulates cellular functions including muscle contraction. Moreover, RLC mutation is associated with cardiomyopathy. To understand the role of RLC in muscle contraction, high-resolution structure in its sarcomeric environment is required. Currently available high-resolution structure of myosin is inadequate to understand the role of RLC. A novel electron microscopy (EM) labelling technique based on APEX2, an engineered variant of soybean ascorbate peroxidase (APEX) protein is a promising technique to resolve the structure of specific protein in its native environment. In this study, the visualisation of the muscle cross-bridge organisation using APEX2 was attained. APEX2 provides the contrast EM by oxidation of di-aminobenzidine (DAB) substrate. For that purpose, fully functional RLCAPEX2 fusion protein was exchanged into muscle fibre. RLC-APEX2 exchanged muscle prepared in the relaxed state showed good ultrastructural preservation and good EM contrast upon chemical fixation. The presence of RLC-APEX2 in myosin cross-bridges permitted us to visualise structural features by electron tomography (ET) in relaxed state. Our standardised APEX2 based EM labelling protocol could be a promising tool for the labelling of other sarcomeric proteins in diseased states, thus permitting the direct visualisation and ultrastructural organisation of muscle proteins by ET.